2018
DOI: 10.1371/journal.pone.0191809
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among children and adolescents: Construct validity, reliability, and parent-adolescent agreement on the ‘Strengths and Difficulties Questionnaire’ in Chile

Abstract: The Strengths and Difficulties Questionnaire (SDQ) is a screening tool used to measure psychological functioning among children and adolescents. It has been extensively used worldwide, but its psychometric properties, such as internal structure and reliability, seem to vary across countries. This is the first study exploring the construct validity and reliability of the Spanish version of SDQ among early adolescents (self-reported) and their parents in Latin America. A total of 1,284 early adolescents (9–15 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 59 publications
(52 reference statements)
6
35
1
3
Order By: Relevance
“…Behavioral strengths and difficulties were assessed using the parent and child versions of the Strengths and Difficulties Questionnaire (SDQ) [48]. The agreement between parent and child reports completed using the SDQ has already been investigated in several studies [18][19][20]26,27]. The questionnaire comprises 25 questions on five different scales: emotional problems (e.g., feeling depressed or anxious), conduct problems (e.g., aggressive behavior, tantrums), hyperactivity/inattention (e.g., being unfocused or restless), peer-relationship problems (e.g., playing alone, having no friends), and pro-social behavior (e.g., being helpful, sharing things).…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral strengths and difficulties were assessed using the parent and child versions of the Strengths and Difficulties Questionnaire (SDQ) [48]. The agreement between parent and child reports completed using the SDQ has already been investigated in several studies [18][19][20]26,27]. The questionnaire comprises 25 questions on five different scales: emotional problems (e.g., feeling depressed or anxious), conduct problems (e.g., aggressive behavior, tantrums), hyperactivity/inattention (e.g., being unfocused or restless), peer-relationship problems (e.g., playing alone, having no friends), and pro-social behavior (e.g., being helpful, sharing things).…”
Section: Plos Onementioning
confidence: 99%
“…Regarding evaluations of mental/physical health of children, several studies have investigated parent-child agreement in reporting behavioral difficulties [18][19][20][21][22][23][24][25][26][27]. Overall, in these studies, parent-child agreement was reported to be moderate [18][19][20][21][22] to high [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean score for each subscale was then calculated (range 0–10) and used in the analyses. The psychometric properties of the self-report version of the SDQ are generally good across studies [14, 15, 16, 17]. The alpha values for each subscale were 0.72 for the emotional symptoms subscale, 0.46 for the conduct problems subscale, 0.59 for the hyperactivity-inattention subscale, 0.55 for the peer problems subscale and 0.66 for pro-social behaviour subscale.…”
Section: Methodsmentioning
confidence: 99%
“…This study did not examine measurement invariance or SDQ factor structure, but the findings suggested that some subscales may have been overreported given the low impact attributed by parents. A recent study by Gaete et al [51] assessing the construct validity and reliability of both the self-reported and parent Spanish language SDQ instruments with Chilean adolescents ages 9–15 and their parents found the original five-factor SDQ structure to perform well. As cited by Gaete et al [51], two additional studies on the SDQ were conducted in Chile.…”
Section: Introductionmentioning
confidence: 99%